The Use of Plant Viral Nanoparticles in Cancer Biotherapy—A Review - Mamorake Donty Komane; Prudence Ngalula Kayoka-Kabongo; Daria Anna Rutkowska (Viruses)
Cancer is a major global health problem that poses significant challenges. Conventional cancer therapies often have severe side effects, necessitating the development of novel therapeutic approaches that are more effective and less toxic. The utilization of plant viral nanoparticles is one of the more promising strategies for cancer biotherapy. Plant viral nanoparticles exhibit advantageous properties, including safety, high stability, rapid production and scalability, biocompatibility and biodegradability, structural uniformity, inherent immunogenicity, ease of modification and high update efficacy as well as lower cost implications, making them attractive vehicles for health applications. Various studies have demonstrated the efficacy of plant viral nanoparticles in targeted therapeutic drug/molecule delivery, tumor imaging and immunotherapy, highlighting their potential as a versatile platform for cancer biotherapy. The drawbacks of plant viral nanoparticles include their perceived ability to induce a hypersensitive/allergic immune response, non-well-defined regulatory approval processes as well as the reluctance of pharmaceutical companies to adapt their manufacturing processes to facilitate plant-based expression. This review discusses applications of plant virus-derived nanoparticles in cancer therapeutics and prospects for translating these findings into clinical practice.